One‐Step Synthesis of White‐Light‐Emitting Carbon Dots for White LEDs with a High Color Rendering Index of 97. Issue 12 (23rd February 2023) - Yan, Zishan; Chen, Tong; Yan, Lingpeng; Liu, Xinghua; Zheng, Jingxia; Ren, Fu‐de; Yang, Yongzhen; Liu, Bin; Liu, Xuguang; Xu, Bingshe
Abstract: White‐light‐emitting carbon dots (WCDs) show innate advantages as phosphors in white light‐emitting diodes (WLEDs). For WLEDs, the color rendering index (CRI) is the most important metric to evaluate its performance. Herein, WCDs are prepared by a facile one‐step solvothermal reaction of trimellitic acid and o ‐phenylenediamine. It consists of four CDs identified by column chromatography as blue, green, yellow, red, and thus white light is a superposition of these four types of light. The mixture of the four CDs undergoes Förster resonance energy transfer to induce the generation of white light. The photoluminescence of WCDs originates from the synergistic effect of carbon core and surface states. Thereinto, the carbon core states dominate in RCDs, and the increase of amide contents and degree of conjugation promote the redshift of the emission spectra, which is further confirmed by theoretical calculations. In addition, a high CRI of 97 is achieved when the WCDs are used as phosphors to fabricate WLEDs, which is almost the highest value up to now. The multicolor LEDs can also be fabricated by using the four multicolor CDs as phosphors, respectively. This work provides a novel approach to explore the rapid preparation of low‐cost, high‐performance WCDs and CDs‐based WLEDs. Abstract : The white‐light‐emitting carbon dots are synthesized by a one‐step solvothermal method of trimellitic acid and o ‐phenylenediamine, which consists of four types of carbon dots emitting blue, green, yellow, and red light. Five kinds of light‐emitting diodes can be prepared using the above carbon dots, among which the color rendering index of white light‐emitting diode is as high as 97.